2021
DOI: 10.1002/adem.202001298
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐Waste Progress for the Synthesis of High‐Purity β‐Sialon Ceramics from Secondary Aluminum Dross

Abstract: Aluminum dross (AD) is a solid waste and the main byproduct that is formed in the process of smelting, consumption, and utilization of aluminum. The volume of the solid waste from aluminum industries is large, and most of these wastes are in the form of waste residues that are meant for accumulation or landfill treatment. [1][2][3] The treatment and reuse of AD is the last link in the production chain in the aluminum industry, and it poses a global challenge. AD can be classified into primary aluminum dross (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The reaction Many studies have reported the formation of SiAlON whiskers using Si and Al-based compounds as starting materials under nitrogen atmosphere, and the vapor-solid (VS) and used vapor-liquid-solid (VLS) growth mechanisms to explain the growth of SiAlON whiskers [44,45]. The composition of synthesis gas (containing SiO and Al 2 O) makes it an important intermediate phase, which significantly influences the preparation and growth mechanism of the whiskers [46]. However, in this study, uniform granules were found in the porous samples instead of whiskers, which may indicate that the gas phase was less involved during the growth process of the SiAlON phase.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction Many studies have reported the formation of SiAlON whiskers using Si and Al-based compounds as starting materials under nitrogen atmosphere, and the vapor-solid (VS) and used vapor-liquid-solid (VLS) growth mechanisms to explain the growth of SiAlON whiskers [44,45]. The composition of synthesis gas (containing SiO and Al 2 O) makes it an important intermediate phase, which significantly influences the preparation and growth mechanism of the whiskers [46]. However, in this study, uniform granules were found in the porous samples instead of whiskers, which may indicate that the gas phase was less involved during the growth process of the SiAlON phase.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis temperature of 1450 • C, holding time of 4 h, and Si-Al ratio of 1:2.5 resulted in β-Sialon powder with a purity exceeding 95 %. 25 Preparation of dense sintered bodies: To ensure homogeneity and eliminate agglomerates in the β-Sialon powder, the prepared powder was subjected to grinding using a planetary ball mill (FP400) for 1 h. The ground powder was then pressed into a mold with a diameter of 10 mm. Subsequently, sintering was performed in a discharge plasma sintering furnace (SPS-211HLABOX 650F) under a pressure of 40 MPa.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Si powder was added to adjust the Si‐Al ratio. The synthesis temperature of 1450°C, holding time of 4 h, and Si‐Al ratio of 1:2.5 resulted in β‐Sialon powder with a purity exceeding 95 % 25 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations